Kinerja organisasi : sistem informasi akuntansi pemerintahan daerah (SIPD), komitmen organisasi dan pengendalian internal - Rahma Sari K, Dwi; Maelani, Puspita; Susilawati, Deti (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
The Regional Development Planning Agency (Bappeda) has a strategic role in the development planning process in Serang City. In regional development, the Serang City Government has a great responsibility to plan and implement development programs that are in accordance with the needs of the local community, but in the field process several problems and obstacles arise, especially in SIPD, organizational commitment, internal control which can affect the performance of Bappeda. This is what hinders regional development. This study aims to determine whether there is an effect of local government accounting information systems (SIPD) and organizational commitment on organizational performance at BAPPEDA of Serang City with internal control as a moderating variable. The method used is quantitative. The population and sample were employees of Bappeda Kota Serang, data collection by distributing questionnaires and data processing using SmartPLS. The results in this study that the Local Government Accounting Information System (SIPD) and organizational commitment have an influence on Organizational Performance. Internal Control as a moderating variable cannot strengthen or weaken the effect of SIPD on Organizational Performance. Conversely, Internal Control can strengthen or weaken the influence of Organizational Commitment on Organizational Performance. Keywords: SIPD, Internal Control, Organizational Commitment, Bappeda Performance, Serang City